2005
DOI: 10.1080/10976640500295417
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Assessment of Regional Myocardial Function with MR-Tagging in a Multi-Center Study: Interobserver and Intraobserver Agreement of Fast Strain Analysis with Harmonic Phase (HARP) MRI

Abstract: Employing the HARP method for quantitative strain analysis of myocardial MR tagged images provides a high inter- and intraobserver agreement. These good results are obtained in case of good to excellent MR image quality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
108
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 121 publications
(117 citation statements)
references
References 23 publications
8
108
1
Order By: Relevance
“…In other MR tagging studies the interobserver variability was approximately the same as in our study using MR tagging (24,25). However, despite the use of harmonic phase (HARP) concepts (26), the data analysis of tagged images is still more time-consuming and is often confounded by noise artifacts due to inadequate image quality (19).…”
Section: Discussionsupporting
confidence: 59%
“…In other MR tagging studies the interobserver variability was approximately the same as in our study using MR tagging (24,25). However, despite the use of harmonic phase (HARP) concepts (26), the data analysis of tagged images is still more time-consuming and is often confounded by noise artifacts due to inadequate image quality (19).…”
Section: Discussionsupporting
confidence: 59%
“…For the ultrasound measurements, this variability was found to be low [24]. For the tagged MR images, a study using the harmonic phase method showed good inter-and intra-observer variability [25]. We only included the midwall layer in the strain analysis, since this region is expected to contain mainly circumferentially oriented myofibers [26].…”
Section: Limitationsmentioning
confidence: 99%
“…We only included the midwall layer in the strain analysis, since this region is expected to contain mainly circumferentially oriented myofibers [26]. In the reproducibility study [25], it was shown that interand intra-observer agreement were best in the midwall layer and increased with improved image quality. In our study, only subjects with good image quality on both modalities were included.…”
Section: Limitationsmentioning
confidence: 99%
“…The CMR parameters were slice thickness of the imaging planes 8 mm with 0 interslice gap, field of view 40 cm, scan matrix 2569128, flip angle 45°, repetition/echo times 3.8/1.6 milliseconds, and number of reconstructed cardiac phases 20. Tagged CMR was done at baseline and post-NTG on exact slice prescriptions as above by applying grid tagging to the short-axis views and stripe tagging to long-axis views using spatial modulation of magnetization encoding gradients method as previously described 10,13 with the following parameters: prospective ECG triggering, repetition/echo times 8.0/4.2 milliseconds, views per segment 8 to 10, tag spacing 7 mm, and number of reconstructed cardiac phases 20. Because the tag lines faded with time due to T1 relaxation, tagged image-derived parameters were valid only throughout systole and the first 67% of diastole.…”
Section: Cardiac Magnetic Resonance Imagingmentioning
confidence: 99%